THE IMPORTANCE OF HEAVY METAL PRODUCTION IN THE SOIL DURING THE GROWTH OF WINTER GRAINS (ResearchJet Journal of Analysis and Inventions, 2021)
Soil microorganisms have mercury-resistant populations that convert metallic mercury into substances that are toxic to developed organisms. Some algae, fungi and bacteria can accumulate mercury in their cells. Heavy metals such as iron, copper, zinc, molybdenum are involved in biological processes and in certain amounts are trace elements necessary for the functioning of plants, animals and the human body.